The Effect of Morning Wake-Up Habits on Elementary School Students’ Learning Readiness In The Perspective of Character Education - Marselina, Linda; Nurulpaik, Iik; Somantri, Mubarok; Supriatna, Encep; Marpian, Marpian (International Conference on Elementary Education, 2025)
Character education and the development of positive habits, such as waking up early, are crucial for fostering self-discipline and ensuring students' readiness to learn, aligning with the global focus on Non-Cognitive Skills (NCS). This study aims to quantitatively measure and analyze the significant effect of the morning wake-up habit intervention on increasing the learning readiness of fifthgrade students at SDN Blokang. A quantitative descriptive approach was employed, involving 32 students in a single class (total sampling) at SDN Blokang. Data were collected via pre-test and posttest questionnaires using a 4-point Likert scale following a two-week intervention period focused on positive morning routines. Analysis showed a substantial positive effect: student learning readiness increased from a mean of 18.75 to 23.10, with the percentage of students in the high category rising from 31.25% to 93.75%. The Pearson correlation coefficient was highly significant at r=0.877 (p<0.05), and the Effect Size was calculated as d=1.36, indicating a very large impact. The consistent, disciplined morning wake-up habit functions as a highly effective behavioral intervention that significantly enhancesstudents' physical, mental, and emotional learning readiness. This provides strong empirical evidence supporting the integration of morning routines as a primary strategy in character education programs